Clinical-anamnestic characteristics and quality of life in patients with the Cajal subtype of chronic slow-transit constipation - Leshchyshyn, I. M.; Markulan, L. Y.; Susak, Y. M.; Okhotska, O. I.; Byk, P. L. (General Surgery, 2025)
The Cajal subtype of chronic slow‑transit constipation (CSTC) is associated with Cajal cell deficienсy and is considered the most resistant to conservative therapy. Its diagnosis requires histological analysis of all layers of the intestinal wall, which involves invasiveness and carries the risk of complications. Therefore, the clinical phenotype of this subtype remains insufficiently studied. Objective – to evaluate the clinical‑anamnestic characteristics and quality of life in patients with the Cajal subtype of chronic slow‑transit constipation following colectomy. Materials and methods. Over the past 12 years, the Cajal histological subtype of CSTC was diagnosed in 21 patients after colectomy (group O). The comparison group included 70 patients of similar age and sex who did not exhibit signs of CSTC (group R). The study groups did not differ significantly regarding gender, mean age, or body mass index. Clinical‑anamnestic data and quality of life were assessed using the PAC‑QOL scale in both groups. Results. Women predominated in both groups: 20 (95.2%) in the main group O and 65 (92.9%) in group R. The mean age was 33.9±8.7 years in group O, compared to 41.5 years in group R. The clinical phenotype of patients with the Cajal subtype who required surgical treatment was characterized by early disease onset at a young age (8.67±5.08 years), a high mean disease duration at presentation (25.24±11.18 years; range 3 – 51), and genetic predisposition, with a positive family history in first‑degree relatives in 50.5% of cases. These patients exhibited prolonged intervals between bowel movements (mean 12.2±4.3 days) and lack of response to conservative therapy. Stool types 1 and 2 on the Wexner scale were observed in 71.4% and 28.6% of patients, respectively. Most patients required manual assistance during defecation (95.2%) and experienced pronounced pain syndrome (visual analog scale 2.8±1.3). Quality of life, as measured by the PAC‑QOL scale, showed a significant decline in group O compared to group R across all parameters. Physical discomfort worsened by 2.72 times (3.24±0.44 vs. 1.19±0.29); psychosocial discomfort by 2.19 times (1.84±0.58 vs. 0.84±0.18); anxiety by 2.66 times (2.05±0.24 vs. 0.77±0.24); satisfaction by 2.88 times (2.48±0.59 vs. 0.86±0.28); and the PAC‑QOL score by 2.57 times (2.24±0.25 vs. 0.87±0.12), with p<0.05 for all comparisons. Conclusions. Our findings confirm the presence of severe clinical and functional disorders in patients with the Cajal subtype, identifying them as potential candidates for surgical treatment.